Implementasi Excellence Public Relations dalam Pengelolaan Konflik oleh Energi Mega Persada Bentu Limited - Genny Gustina Sari; Gasela Hardianti (CoverAge: Journal of Strategic Communication, 2021)
Energi Mega Persada (EMP) Bentu Ltd is a national oil and gas company that operates the Bentu Block located in Riau Province. The increasing number of EMP Bentu Ltd consumers is directly proportional to the increasing number of gas wells, which causes EMP Bentu Ltd to often come into conflict with the community around the well. This study aims to determine the implementation of excellence public relations in conflict management by Public Relations Energi Mega Persada Bentu Limited in Muara Sakal District. Pelalawan 2019 through conflict management in carrying out the direction of communication, maintaining a balance of interests, running communication channels and considering the level of ethnicity. This study used qualitative research methods. Determination of informants using snowball sampling technique with 3 (three) informants at EMP Bentu Ltd and 7 (seven) people involved in Focus Group Discussion (FGP) in Muara Sakal Hamlet. The results of this study indicate PR EMP Bentu Ltd in managing conflict in Muara Sakal implements public relations excellence put forward by James E. Grunig and Hunt through implementation in carrying out the direction of conflict communication, maintaining a balance of interests, running communication channels and considering the level of ethnicity through conflict management. . Although unable to apply the 10 principles of excellent PR perfectly due to overlapping division of tasks, the conflict management in Muara Sakal Hamlet can be resolved.